Kajian Hukum Pencabutan Hak Politik Pada Pelaku Tindak Pidana Korupsi Suap Berdasarkan Teori Kepastian Hukum - Chintya Devi (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2021)
Criminal sanctions are sanctions imposed by a judge in court on a person who has committed a criminal act or is known as a defendant. In Indonesia, criminal sanctions are divided into two, namely the main criminal sanctions and additional criminal sanctions listed in article 10 and article 35 of the Criminal Code. The imposition of additional penalties cannot stand alone but there must be primary criminal sanctions in advance. In connection with the conviction of a person, there is a need for legal objectives, one of which is legal certainty. Perpetrators of bribery corruption in imposing sanctions need a deterrent effect for the perpetrators. In this study the authors used a normative juridical research method with data collection techniques used to solve problem formulations, namely official documents, laws and regulations, official books and interviews. The purpose of this study is to analyze the elements of the imposition of additional criminal sanctions for depriving political rights of the perpetrators of bribery corruption with the realization of the principle of legal certainty.